2009
DOI: 10.1016/j.cell.2008.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of a Bacterial Condensin Complex Reveal ATP-Dependent Disruption of Intersubunit Interactions

Abstract: Condensins are key mediators of chromosome condensation across organisms. Like other condensins, the bacterial MukBEF condensin complex consists of an SMC family protein dimer containing two ATPase head domains, MukB, and two interacting subunits, MukE and MukF. We report complete structural views of the intersubunit interactions of this condensin along with ensuing studies that reveal a role for the ATPase activity of MukB. MukE and MukF together form an elongated dimeric frame, and MukF's C-terminal winged-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
287
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(307 citation statements)
references
References 29 publications
(44 reference statements)
17
287
2
1
Order By: Relevance
“…MukF stimulation of the MukB ATPase was maximal at the substoichiometric ratio of MukF to MukB of 1:4. This observation seems somewhat at odds with structural studies showing that the MukF dimer binds at the bottom (compared with the orientation of the coiled-coil regions) of the MukB head domain dimer and that ATP hydrolysis causes the head domain dimer to come apart, with one MukF monomer becoming largely dissociated from the complex, leaving only a flexible linker bound to one of the monomers of the MukB head domain (23).…”
Section: Topological Alteration Of the Dna Observed In The Reactions contrasting
confidence: 44%
See 3 more Smart Citations
“…MukF stimulation of the MukB ATPase was maximal at the substoichiometric ratio of MukF to MukB of 1:4. This observation seems somewhat at odds with structural studies showing that the MukF dimer binds at the bottom (compared with the orientation of the coiled-coil regions) of the MukB head domain dimer and that ATP hydrolysis causes the head domain dimer to come apart, with one MukF monomer becoming largely dissociated from the complex, leaving only a flexible linker bound to one of the monomers of the MukB head domain (23).…”
Section: Topological Alteration Of the Dna Observed In The Reactions contrasting
confidence: 44%
“…Our observations are consistent with these previous observations; however, we observe distinct inhibition of the MukB-mediated catenation reaction by the addition of ATP, with less inhibition observed with AMP-PNP, and no inhibition observed with ADP. The binding of AMP-PNP is known to bring the head domains together (23). Thus, the observation that AMP-PNP does not inhibit the catenation reaction to the same extent as ATP suggests that it is not the closing of the MukB head domains per se that is inhibitory, but the cycling between the closed and open conformations supported by the presence of ATP.…”
Section: Topological Alteration Of the Dna Observed In The Reactions mentioning
confidence: 82%
See 2 more Smart Citations
“…Similarly, the MukBEF complex remains stably associated with the E. coli chromosome following cell lysis, suggesting that this complex also serves a scaffolding role that organizes the bacterial chromosome into a higher-order structure (71). Electron microscopy studies have revealed that MukBEF complexes can aggregate to form rosettes (72), and high-resolution structural studies suggest that this process may occur through MukF/E mediated bridging of MukB dimers (73).…”
Section: Discussionmentioning
confidence: 99%